2016
DOI: 10.1016/j.bbagen.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A small peptide promotes EphA2 kinase-dependent signaling by stabilizing EphA2 dimers

Abstract: BACKGROUND The EphA2 receptor tyrosine kinase is known to promote cancer cell malignancy in the absence of activation by ephrin ligands. This behavior depends on high EphA2 phosphorylation on Ser897 and low tyrosine phosphorylation, resulting in increased cell migration and invasiveness. We have previously shown that EphA2 forms dimers in the absence of ephrin ligand binding, and that dimerization of unliganded EphA2 can decrease EphA2 Ser897 phosphorylation. We have also identified a small peptide called YSA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 63 publications
4
24
0
Order By: Relevance
“…This controlled osmotic stress leads to disassembly of the caveolae, which are 60–80 nm cup-shaped invaginations of the plasma membrane 43 . The application of the reversible osmotic stress does not cause irreversible cell damage, and thus quantitative biophysical experiments can be performed in live cells 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…This controlled osmotic stress leads to disassembly of the caveolae, which are 60–80 nm cup-shaped invaginations of the plasma membrane 43 . The application of the reversible osmotic stress does not cause irreversible cell damage, and thus quantitative biophysical experiments can be performed in live cells 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…As a member of RTK family, it is well known that EphA2 is an emerging target for cancer therapeutics, due to its increased expression in tumor tissues [ 12 14 ]. Downregulation of EphA2 expression through various approaches inhibits malignant behavior in vitro and in vivo [ 31 33 ]. To date, the knowledge of functional roles and regulatory mechanism of EphA2 in GC are remains unclear due to the lack of applicable and practicable method to target it.…”
Section: Discussionmentioning
confidence: 99%
“…Using a quantitative FRET approach in live cells, we have previously shown that in HEK293 cells transiently transfected with EphA2, the receptor weakly dimerizes in the absence of a bound ligand (22) through an extracellular interface known as the "clustering" interface (19,20). Furthermore, we found that the YSA-GSGSK (3) peptide increases the formation of these EphA2 unliganded dimers (23,24). In contrast, the monomeric , total EphA2 levels, and AKT phosphorylation on Ser 473 (pAKT, indicative of AKT activation).…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signaling mentioning
confidence: 95%
“…Whereas nonbiotinylated peptides can induce weak EphA2 tyrosine phosphorylation when present at very high concentrations, or when the receptor is highly expressed by transient transfection (24), at lower concentrations, these peptides mainly function as antagonists that inhibit EphA2 signaling by an activating ligand, such as ephrin-A1 Fc. Interestingly, recent FRET studies have revealed that the nonbiotinylated YSA-GSGSK (3) increases the proportion of EphA2 dimers assembled through the clustering interface.…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signalingmentioning
confidence: 99%